Efektifitas Pertumbuhan Benih Betok (Anabas testudineus) Menggunakan Vitamin C dan D sebagai Suplemen Pakan - Helmizuryani Helmizuryani; Meika Puspitasari; Khusnul Khotimah (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Helmizuryani et al, 2018. Growth Effectivity of Climbing Perch (Anabas testudineus) Used Vitamin C and D as Feed Suplement. JLSO 7(2):164-173.Â The added of vitamin in feed is expected to increase the feed efficiency ,growth and survival of climbing perch (Anabas testudineus). This research was conducted to analysis the effectivity of vitamin supplement to increased the growth and survival of climbing perch (Anabas testudineus). The method used was an experimental method, with Completely Randomized Design (CRD), and three levels of treatment. The research carried out at Fish Hatchery Unit named Mulia on Plaju district, Palembang city. It's started from March until May 2018. The treatment used vitamin C and D gives the doses differentiation, that were V1 (doses of vitamin C 125 mg/kg feed), V2 (doses of vitamin D 375 mg/kg feed), and V3 (doses of vitamin C + D 125 mg/kg feed and 375 mg/kg feed). The growth analysis parameter was the growth of length, weight, and survival rate. The results that showed the best growth and survival of climbing perch (Anabas testudineus) were vitamin D and C, where best mass on V3 about 3,89 g. While the lowest on V1 about 2,7g. The best growth length on V3 about 4,61 cm, otherwise the weakest on V1 about 3,85 cm. The survival rate was highest on V3 about 88,33% and the lowest on V2 about 83,33%. Vitamin required for a fish body to carry out metabolism, but if overuses could be hipervitaminosis.Â